Oxaliplatin, fluorouracil, and leucovorin with or without cetuximab in patients with resected stage III colon cancer (PETACC-8): an open-label, randomised phase 3 trial - Taieb, Julien; Tabernero, Josep; Mini, Enrico; Subtil, Fabien; Folprecht, Gunnar; Van Laethem, Jean-Luc; Thaler, Josef; Bridgewater, John; Petersen, Lone Nørgård; Blons, Hélène; Collette, Laurence; Van Cutsem, Eric; et al. (The lancet oncology, 2014)
Since the 1990s, fluorouracil-based adjuvant chemotherapy has significantly reduced the risk of tumour recurrence in patients with stage III colon cancer. We aimed to assess whether the addition of cetuximab to standard adjuvant oxaliplatin, fluorouracil, and leucovorin chemotherapy (FOLFOX4) in patients with stage III colon cancer improved disease-free survival (DFS). For this open-label, randomised phase 3 study done in nine European countries, we enrolled patients through an interactive voice response system to the central randomisation centre, with a central stratified permuted block randomisation procedure. We randomly assigned patients with resected (R0) stage III disease (1:1) to receive 12 cycles of FOLFOX4 twice a week with or without cetuximab. Patients were stratified by N-status (N1 vs N2), T-status (T1-3 vs T4), and obstruction or perforation status (no obstruction and no perforation vs obstruction or perforation or both). A protocol amendment (applied in June, 2008, after 2096 patients had been randomly assigned to treatment-restricted enrolment to patients with tumours wild-type at codons 12 and 13 in exon 2 of the KRAS gene (KRAS exon 2 wild-type). The primary endpoint was DFS. Analysis was intention to treat in all patients with KRAS exon 2 wild-type tumours. The study is registered at EudraCT, number 2005-003463-23. Between Dec 22, 2005, and Nov 5, 2009, 2559 patients from 340 sites in Europe were randomly assigned. Of these patients, 1602 had KRAS exon 2 wild-type tumours (intention-to-treat population), 791 in the FOLFOX4 plus cetuximab group and 811 in the FOLFOX4 group. Median follow-up was 3·3 years (IQR 3·2–3·4). In the experimental and control groups, DFS was similar in the intention-to-treat population (hazard ratio [HR] 1·05; 95% CI 0·85–1·29; p=0·66), and in patients with KRAS exon 2/BRAF wild-type (n=984, HR 0·99; 95% CI 0·76–1·28) or KRAS exon 2-mutated tumours (n=742, HR 1·06; 95% CI 0·82–1·37). We noted heterogeneous responses to the addition of cetuximab in preplanned subgroup analyses. Grade 3 or 4 acne-like rash (in 209 of 785 patients [27%] vs four of 805 [<1%]), diarrhoea (113 [14%] vs 70 [9%]), mucositis (63 [8%] vs 10 [1%]), and infusion-related reactions (55 [7%] vs 30 [4%]) were more frequent in patients treated with FOLFOX4 plus cetuximab than in those patients who received FOLFOX4 alone. The addition of cetuximab to FOLFOX4 did not improve DFS compared with FOLFOX4 alone in patients with KRAS exon 2 wild-type resected stage III colon cancer. This trial cannot conclude on the benefit of cetuximab in the studied population, but the heterogeneity of response suggests that further investigation of the role of FOLFOX4 plus cetuximab in specific patient subgroups is warranted. Fédération Francophone de Cancérologie Digestive (FFCD), Merck KGaA, and Sanofi-Aventis.